Illiquid banks in an overly liquid sector. The impact of liquidity regulation on the deposit policy of listed banks in Poland - Czaplicki, Marcin (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: The article aimed to show that banks may face liquidity issues even in a structurally over-liquid sector. The relation between monetary policy and liquidity regulations (liquidity coverage ratio, LCR) was outlined, showing that changes in regulatory liquidity, in the form of the surplus over LCR requirement, impact banks’ deposit policy. Methodology: The author employed qualitative and quantitative data analysis, including dynamic panel data modelling and the calculation of the beta coefficient, presenting the response of deposit policy to changes in the central banks’ reference rate. Results: It was found that the scale of bank interest rate increases in Poland was visibly higher than in the most of EU countries, among others as a result of the decrease in LCR ratios, which in turn was conditioned by the structural features of the Polish banking sector, namely the high exposure to interest rate risk on securities. Implications and recommendations: The presence of the macroprudential (liquidity) policy channel may reinforce monetary policy transmission via its impact on banks’ deposit policy. Originality/value: The article contributes to the emerging literature on the bank deposit channel of monetary policy transmission. Moreover, it outlines a new (liquidity part of the) macroprudential channel of monetary policy transmission and its operation in Poland during the interest rate tightening cycle.
Argumenta Oeconomica, 2025, Nr 2 (55), s. 133-150
Keywords: monetary policy; banks; liquidity requirements; transmission; deposits; interest rates